Extracellular vesicles secreted by model tapeworm Hymenolepis diminuta: biogenesis, ultrastructure and protein composition - Mazanec, Hynek; Koník, Peter; Gardian, Zdenko; Kuchta, Roman (International journal for parasitology, 2021)
We provided the first known evidence of the presence and release of extracellular vesicles in adults of important model tapeworm Hymenolepis diminuta. Two different subtypes have been observed on the surface of the worm and among the secretory products confirmed by several microscopical methods. Proteomic analysis revealed the presence of parasite-specific proteins as well as those of the host in purified extracellular vesicles. Among the protein cargo, we identified potential drug targets, vaccine candidates and H. diminuta antigens. Finally, the protein composition further revealed proteins participating in the endosomal complex required for transport-dependent biogenesis pathway.
Keywords: Animals; cestodózy; Electron microscopy; Proteomics; Cestode Infections; Proteins; zvířata; Extracellular Vesicles; proteomika; Host-Parasite Interactions; Secretion; interakce hostitele a parazita; Hymenolepis; extracelulární vezikuly; Hymenolepis diminuta; LC–MS/MS; Size exclusion chromatography; Exosomes